Policy Analysis of Teacher Professional Improvement in YPPSB Elementary School - Sismanto Sismanto (International Journal of Asian Education, 2021)
The purpose of the research was to identify policy formulation, policy implementation, policy environment, and performance professional improvement of teachers in the elementary school of YPPSB. This policy research used a qualitative approach. The data of this research was collected by in-depth interviews, observation, documentation study. Analysis of data using a technique of organizing data, coding, verification, and conclusions). This research's findings are as follows: (1) policy of the teacher professional improvement of SD YPPSB - PT. Kaltim Prima Coal follows a Top-down approach and bottom-up approach model of formulation policy, (2) the implementation of teacher professional improvement policy successfully conducted to its vision, mission, and goal; (a) recruitment of qualification teachers, (b) Conducting and includes teachers in the education and training, (c) professionalization of teachers through KKG and MGMP, (d) facilitating teachers to continue their studies S2, (e) educational supervision, ( f) course intensification, (g) weekly meeting, (h) reward, and (i) allowance. Policy recommendations that can be given are as follows, (1) Principal of SD YPPSB needs to increase teachers' professional development, primarily through forms of training, (2) the Education Department to develop comprehensive education, especially for private schools, and (3) The Government continually strive to find alternatives to increase the professionalism of teachers.